Web-Based spatial data interaction mechanism supporting open-source GIS application for GIS in school / Mohd Khairy Kamarudin … [et al.] - Kamarudin, Mohd Khairy; Mat Arof, Zakaria; Abd Samad, Mohd Adhar; Mohd Hashim, Norshahrizan (Research Management Institute, 2016)
Geographical Information System (GIS) is a computer system for capturing, storing, querying, analyzing and displaying geospatial data. GIS is synonymous with geographical subjects in school. Geography Interactive Training Module (GISKIT) would be created to be used by teachers and students in the academic session. The module was created using spatial and attributes data that was collected during the study. Actually, GIS can enhance geography teaching and provides information about useful resources. So, the purpose to the study is mainly to create a module GISKIT using web based application for the teaching and learning geography subjectthat will develop a spatial thinking availability among students using web based applicationThis project also to study the effectiveness of the module GISKIT compared with current method where only used geography textbook to teach students. Hopefully this module also will be used widely to all schools in Malaysia.